Mutual Fund Investment in Emerging Markets : An Overview - Kaminsky, Graciela L.; Lyons, Richard K.; Schmukler, Sergio L. (Washington, DC: World Bank, 2014)
International mutual funds are key contributors to the globalization of financial markets and one of the main sources of capital flows to emerging economies. Despite their importance in emerging markets, little is known about their investment allocation and strategies. This article provides an overview of mutual fund activity in emerging markets. It describes their size, asset allocation, and country allocation and then focuses on their behavior during crises in emerging markets in the 1990s. It analyzes data at both the fund-manager and fund-investor levels. Due to large redemptions and injections, funds' flows are not stable. Withdrawals from emerging markets during recent crises were large, which is consistent with the evidence on financial contagion.